Identification and characterization of the cell division protein MapZ from Streptococcus suis. Issue 5 (8th October 2021) - Dresen, Muriel; Rohde, Manfred; Arenas, Jesús; de Greeff, Astrid; Nerlich, Andreas; Valentin‐Weigand, Peter
Abstract: Streptococcus suis, an emerging zoonotic pathogen, causes invasive diseases in pigs, including sepsis, meningitis, endocarditis, pneumonia, and arthritis. Importantly, similar pathologies are reported in human S .  suis infections. In previous work, the locus SSU0375 of S .  suis strain P1.7 had been identified as a conditionally essential gene by intrathecal experimental infection of pigs with a transposon library of S .  suis . This study aimed to identify the function of the corresponding gene product. Bioinformatics analysis and homology modeling revealed sequence and structural homologies with the Streptococcus pneumoniae mid‐cell‐anchored protein Z (MapZ) that is involved in cell division in different bacterial species. Indeed, depletion of this locus in S .  suis strain 10 revealed a growth defect as compared to the wild type. Electron microscopy analysis of the corresponding mutant demonstrated morphological growth defects as compared to the wild‐type strain, including an irregular cell shape and size as well as mispositioned division septa. Light microscopy and subsequent quantitative image analysis confirmed these morphological alterations. In the genetic rescue strain, the wild‐type phenotype was completely restored. In summary, we proposed that SSU0375 or the corresponding locus in strain 10 encode for a S .  suis MapZ homolog that guides septum positioning as evidenced for other members of the Streptococci family. Abstract : The mid‐cell anchored protein Z (MapZ) is involved in cell division in Streptococcus suis, an emerging zoonotic pathogen. The deletion of this gene leads to morphological growth defects including aberrant cell shapes and sizes as well as mispositioned division septa. Moreover, the absence of MapZ results in reduced biological fitness in the host.